Platelets prevent the development of monocrotaline-induced liver injury in mice. (15th December 2020) - Otaka, Fumisato; Ito, Yoshiya; Goto, Takuya; Eshima, Koji; Amano, Hideki; Koizumi, Wasaburo; Majima, Masataka
Highlights: MCT-induced liver injury is accompanied by thrombocytopenia. Induction of thrombocytopenia exacerbates liver injury. Pretreatment with TPO or a TPO receptor agonist attenuates liver injury. Platelets attenuate liver injury by protecting liver sinusoidal endothelial cells. Abstract: Destruction of liver sinusoidal endothelial cells (LSECs) is an initial event in sinusoidal obstruction syndrome (SOS) that leads to accumulation of platelets in the liver. Herein, we explored the role of platelets during progression of experimental SOS induced by monocrotaline (MCT) in mice. Depletion of platelets using an anti-CD41 antibody or anti-thrombocyte serum exacerbated MCT-induced liver injury in C57BL/6 mice, as indicated by an increase in the alanine transaminase (ALT) level, which was associated with hemorrhagic necrosis. Thrombocytosis induced by thrombopoietin (TPO) or the TPO receptor agonist romiplostim (ROM) attenuated MCT-induced liver injury, as evidenced by lower levels of ALT and mRNA encoding matrix metalloproteinase (MMP) 9, and higher levels of mRNA encoding vascular endothelial growth factor receptor (VEGFR) 2 and VEGFR3. The level of activated hepatic platelets was higher in TPO- and ROM-treated mice than in saline-treated mice. Co-culture with a high number of platelets increased the viability of LSECs and their mRNA levels of CD31, VEGFR2, and VEGFR3, and decreased their mRNA level of MMP9. The level of VEGF-A was increased in the culture medium of LSECs co-cultured with platelets. These results indicate that platelets attenuate MCT-induced liver injury by minimizing damage to LSECs.